Against the Tide: A Critical Review by Scientists of How Physics and Astronomy Get Done edited by Martin Lopez Corredoira and Carlos Castro Perelman - Westrum, Ron (Journal of Scientific Exploration, 2016)
When, many years ago, I frequented the Physics Library of the University of Michigan, there was a cabinet that held a number of books that were characterized as “Weird Physics,” or some similar title. As I recall, the books were kept under glass and locked up. I can only wonder if it is still there, or whether other Physics Departments have some similar arrangement. (And not only Physics Departments!) But what happens to the humans who write such books? No longer are they burned at the stake (like Giordano Bruno), held under house arrest (like Galileo), or consigned to prison (Cf. USSR). But they have their punishments, nonetheless. All members of the Society for Scientific Exploration (SSE), I am sure, know the high price to be paid for the research of taboo topics. Many have experienced the subtle, and sometimes not so subtle, hints to forget the subject altogether. Others have experienced the early derailment or termination of otherwise promising careers, the snickering dismissal by the toadies of dominant paradigms, and the worse consignment of taboo researchers by the powerful to various academic limbos for looking into forbidden subjects. The temptation to present my own trials is strong, but I will resist it. For we all have our own stories to tell. And we all hope for historical vindication.